Apoptosis induction and tumor growth suppression by hydroxyapatite nanoparticles–cisplatin combined treatment in Ehrlich solid carcinoma-bearing mice - Shaymaa M. Eissa; Asmaa M. Mahfouz; Saad M. El-Gendy; Al-shimaa Zakaria; Heba Effat; Hanan R. H. Mohamed (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background Hydroxyapatite (HAP) resembles the components of biological hard tissue. Recent research has been interested in the biomedical application of HAP nanoparticles (HAP-NPs) in cancer treatment, HAP-NPs have high cytotoxic activity against cancerous cells, in addition, they are nontoxic to healthy normal cells, biocompatible, biodegradable, and have a high absorption rate within the tissue. Therefore, this study evaluated HAP-NPs' antitumoral activity in Ehrlich solid carcinoma (ESC)-bearing mice, in addition, we examined the anticancer efficacy of combined treatment of a common chemotherapeutic drug such as Cisplatin (CDDP) and HAP-NPs in ESC-bearing mice. Methods Forty female mice were inoculated with 200 µl of diluted ascites fluid containing approximately two million viable cancer cells in the mice's left thigh, after 14 days of inoculation, the mice were distributed into four groups: 10 mice in each. ESC group was administrated distilled water, the HAP-NPs group was treated orally with 100 mg/kg of hydroxyapatite nanoparticles, the CDDP group was administrated intraperitoneally with 5 mg/kg of Cisplatin, the HAP-NPs + CDDP group was treated with both doses of hydroxyapatite and cisplatin, the animal treatment was conducted for 20 days. Antitumor activity was assessed for two durations after 10 and 20 days. DNA damage assessment was performed using comet assay in ESC, in addition, we measured the expression of the following genes (P53, Bcl2, and Bax,) using quantitative real-time PCR, and the apoptotic-related proteins (P53 and Ki-67) using immunohistochemical analysis. A histopathological examination of ESC was performed. Results The obtained data illustrated a promising anticancer activity of HAP-NPs, and the combined treatment of HAP-NPs and CDDP illustrated a higher anticancer efficacy. HAP-NPs, CDDP, and HAP-NPs + CDDP resulted in significant (P < 0.05) nucleic acid destruction, and significant (P < 0.05) overexpression of apoptotic-related genes (P53, Bax, and Bcl2) and proteins (Ki-67 and P53), causing the tumor bulk to be greatly reduced in HAP-NPs, CDDP, and HAP-NPs + CDDP (1100, 570, and 450 mm3), respectively, compared to ESC group was 2240 mm3. Conclusion Hydroxyapatite nanoparticles can provoke DNA damage and regulate apoptosis, selectively eliminating tumor cells. The co-administration of HAP-NPs and CDDP resulted in a synergistic enhancement of cisplatin activity within the tumor tissue.